2022
DOI: 10.3389/fmicb.2022.885978
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome single nucleotide polymorphism analysis for typing the pandemic pathogen Fusarium graminearum sensu stricto

Abstract: Recent improvements in microbiology and molecular epidemiology were largely stimulated by whole- genome sequencing (WGS), which provides an unprecedented resolution in discriminating highly related genetic backgrounds. WGS is becoming the method of choice in epidemiology of fungal diseases, but its application is still in a pioneer stage, mainly due to the limited number of available genomes. Fungal pathogens often belong to complexes composed of numerous cryptic species. Detecting cryptic diversity is fundame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 76 publications
1
6
0
Order By: Relevance
“…Our study also identified a small A1 population, which consistently with our previous findings [ 20 ], was placed close to the root of the F . graminearum lineage on the phylogenomic tree ( Fig 1B ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our study also identified a small A1 population, which consistently with our previous findings [ 20 ], was placed close to the root of the F . graminearum lineage on the phylogenomic tree ( Fig 1B ).…”
Section: Discussionsupporting
confidence: 92%
“…Among the total of 96 strains used in this study, 82 were chosen to maximize geographic diversity in Europe with regard to the previous phylogenomic approach [ 20 ]. In addition, to enhance the diversity of the sample, we included twelve strains recovered outside of Europe.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the whole-genome sequences of all 16 species, including Fusarium sp. CBS 123663, was reported [ 34 , 35 , 36 ], and FGSG_17538 or its homolog was detected in nine species, constituting a subclade in the phylogenomic tree of the Fg complex [ 36 ]. Furthermore, positive amplification by PCR with HS976/HS1039 primers was observed for F. boothii , which belongs to the African clade ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%